The “Comorbid Patient” Scale as a General practitioner’s tool to increase treatment adherence in patients living in rural areas - T. E. Morozova; T. S. Popova; E. A. Barabanova; E. O. Samokhina (Сеченовский вестник, 2020)
Aim. To develop a visual aid “Comorbid patient Scale” and evaluate its effectiveness through dynamic follow-up of patients with chronic non-communicable diseases (NCDs) in outpatient practice.Materials and methods. The prevalence of risk factors and NCDs were analyzed in the course of a retrospective study of 1444 patients in rural areas. A visual aid “Comorbid Patient Scale” developed on obtained data has been evaluated in a 3-month prospective comparative study of 93 patients with NCDs, randomized to group 1, in which the Scale was used (n = 47), and a control group (group 2, n = 46).Results. Group 1 showed a statistically significant increase in adherence to treatment after using the Scale for 3 months: 81% vs 57% at baseline (p < 0.05); in group 2 similar indicators were: 61% vs 54% (the difference is not significant). In group 1, the proportion of smoking patients (39% vs 15% (p < 0.05)) and the number of patients with hypercholesterolemia (23% vs 0% (p < 0.05)) significantly decreased; the number of patients with well-controlled arterial hypertension increased from 47% to 87% (p < 0.05). A similar dynamics was observed in group 2, however, the difference was not statistically significant. At baseline and 3 months later, the share of patients without exacerbation of diseases of the musculoskeletal system and respiratory tract diseases was the same across the groups.Conclusion. The use of “Comorbid patient Scale” compared to standard patient management increases patient adherence to treatment by 17%, reduces the share of smoking patients by 21%, with hypercholesterolemia by 14%, with the achievement of target blood pressure indicators by 26%.